Influence of Knowledge Sharing, Innovation Capacity, Firm Performance in Nigerian Agro-clusters - Isiaka Kolawole Mustapha; Olalekan Busra Sakariyau; Mercy M Adeyeye; Abdul Falilat Ajoje (Inclusive Society and Sustainability Studies, 2023)
Collaboration and cooperation among entrepreneurs and enterprises have created strategies to improve well-being and create sustainable businesses to foster regional development. Therefore, this paper investigates the relationship between knowledge sharing, innovation and socio-economic growth of micro, small and medium enterprises (MSMEs) in Nigeria's rabbit farming e-clusters space. The web survey method was adopted by employing five Likert scale questionnaires through social media platforms respondents. 78 valid respondents were collected from MSMEs in rabbit farming e-clusters. The hypothesis was tested using the structural equation modelling (SEM) approach. The finding suggests knowledge sharing, innovation capacity, and firm performance positively influence the socio-economic growth of rabbit farmers in e-cluster. Social media platforms, including WhatsApp, Facebook and Telegram, prove that farmers not in the same geographical location are not a barrier to the benefit of clusters. This study proposes that knowledge sharing, innovation capacity and firm performance within an e-cluster improved the socio-economic growth of farmers. The acceptance of a physical-less business cluster that would reduce the rural-urban migration of agribusiness can be achieved. This study contributes to the literature on knowledge transfer, innovation and firm performance in e-cluster rabbit farming. A new dimension to the Industrial Cluster model by adapting to a virtual agglomeration of business and social media platforms.